THE SYSTEM OF DEVELOPING SPEECH AND THINKING THROUGH MODERN PEDAGOGICAL TECHNOLOGIES (International journal of artificial intelligence, 2026)
The modernization of the educational system in Uzbekistan has significantly increased the importance of developing students’ speech and thinking abilities through modern pedagogical technologies. Contemporary education requires learners who are capable of independent reasoning, creative analysis, effective communication, and active participation in social life. In this context, the integrated development of speech and thinking has become one of the central objectives of pedagogical science and educational practice. This scientific article examines the theoretical and methodological foundations of developing speech and thinking through modern pedagogical technologies on the basis of Uzbek scientific and educational literature. The article analyzes the interrelationship between speech and thinking, the role of innovative educational methods, digital pedagogy, communicative approaches, interactive teaching strategies, problem-based learning, project technologies, collaborative learning, multimedia education, and information technologies in the intellectual and communicative development of learners. Particular attention is devoted to the pedagogical conditions that support the formation of speech competence, critical thinking, analytical reasoning, and creative activity in students. The study also highlights the significance of learner-centered educational models and competency-based approaches in modern educational practice. The article demonstrates that modern pedagogical technologies increase educational efficiency, strengthen learners’ motivation, and stimulate active cognitive and communicative participation. Furthermore, the research emphasizes the role of teachers in organizing innovative educational environments that encourage dialogue, intellectual inquiry, and independent learning. Based on Uzbek pedagogical experience and scientific research, the article concludes that modern pedagogical technologies create broad opportunities for developing students’ speech culture, thinking abilities, communicative competence, and intellectual independence, thereby contributing to the formation of harmoniously developed individuals capable of adapting successfully to contemporary social and technological conditions.